TANGGAPAN PERSEPTUAL GURU BAHASA INGGRIS DI SD SE-SURAKARTA TERHADAP KEBIJAKAN PELAKSANAAN MATA PELAJARAN BAHASA INGGRIS DI SEKOLAH DASAR - Honest Ummi Kaltsum (Profesi Pendidikan Dasar, 2014)
This qualitative descriptive study aims to describe how the perceptual response of teachersof English in primary schools towards the government policy related to the implementationof English subjects in elementary school. Population of this research is Englishteachers at the elementary school in Surakarta and takes a sample of English teachersfrom primary schools in partnership with UMS PGSD as many as 20 teachers ofEnglish. Methods of data collection in this study using observations, interviews anddocumentation, and analysis with interactive analysis. In this research, the elementaryteachers as research respondents divided into two groups of teachers who have educationalbackgrounds of English and non-English language. These two groups, dividedinto four categories. The first category are teachers who have a background in Englisheducation with teaching experience less than or equal to ten years. The second categoryare teachers with educational background in English with teaching experience morethan ten years. The third categoryare teachers with backgrounds non English with teachingexperience less than ten years. The fourth category are teachers with backgroundsnon English with teaching experience more than ten years. The findings found in perceptualresponse from the four categories of teachers, show that basically they comprehendthat the implementation of English subjects in elementary school is very importantdue to many reasons. The teachers agree toward the implementation of Englishsubject at elementary school as long as it is conducted seriously and in a professionalways rather than as a additional curriculum.